Ժամանակակից հայերենի ու պարսկերենի անվանական հարադրությունների ընդհանրությունները - Իսա Ալիռեզայի (ՀՀ ԳԱԱ հրատ.)
This article briefly presents the main types of nominal analytical compounds in Armenian and Persian.
Keywords: Language and Literature